2014
DOI: 10.4238/2014.june.9.6
|View full text |Cite
|
Sign up to set email alerts
|

Water buffalo genome characterization by the Illumina BovineHD BeadChip

Abstract: ABSTRACT. To define the best strategies for genomic association studies and genomic selection, it is necessary to determine the extent of linkage disequilibrium (LD) and the genetic structure of the study population. The current study evaluated the transference of genomic information contained in the Illumina BovineHD BeadChip from cattle to buffaloes, and assessed the extent of the LD in buffaloes. Of the 688,593 bovine single nucleotide polymorphism (SNP) that were successfully genotyped from the 384 buffalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…In our study, we found a total of 20 479 SNP polymorphic in water buffalo and a call rate of 86%. In a similar study, 16 580 SNPs were found in 384 swamp type samples at a similar call rate (85%; Borquis et al, 2014). Our higher number of SNPs is mostly due to the use of swamp and river buffalo samples in our testing.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In our study, we found a total of 20 479 SNP polymorphic in water buffalo and a call rate of 86%. In a similar study, 16 580 SNPs were found in 384 swamp type samples at a similar call rate (85%; Borquis et al, 2014). Our higher number of SNPs is mostly due to the use of swamp and river buffalo samples in our testing.…”
Section: Discussionsupporting
confidence: 64%
“…However, water buffalo (B. bubalis) and cattle (Bos taurus) are phylogenetically very close, have an high chromosomal homology between species and share gene order and chromosome banding homology (Borquis et al, 2014). Therefore, buffalo studies can benefit of genomic tools developed for cattle, to gather genome-wide diversity information of the buffalo populations.…”
Section: Introductionmentioning
confidence: 99%
“…Since there was no literature regarding the analysis of this polymorphism, it was not possible to comment on the STAT5A-AvaI polymorphism in different buffalo breeds. However, it was thought that it could be compared with the results obtained in different cattle breeds due to the high rate of homology of the water buffalo genome with the cattle genome from many gene aspects [35,36]. On the other hand, it was thought that these genes showed homology in cattle and water buffalo because of obtaining the reported-sized PCR products in cattle at the end of the conducted PCR process and cleaving the obtained PCR products with the reported restriction enzymes in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…As water buffalo and yellow cattle are both members of the Bovidae family, they are closely related, and the vast amount of cattle genomic resources might serve as shortcuts for further advances genome science and biotechnology in this species [ 32 ]. In 2014, the water buffalo genome research group also declared that the bovine genome could be utilized in association studies [ 33 ]. In this paper, a Bos taurus genome-wide gene chip was used to analyze and compare the overall gene expression profiles of peripheral blood from water buffalo and yellow cattle, both pre- and post infection with S .…”
Section: Discussionmentioning
confidence: 99%